Features of Self-Dependence in the Activity of Students, Future Technology Teachers - Dačiulytė, Rūta (Acta Paedagogica Vilnensia, 2004)
Students’ self-dependence in their activity and the model of its research is described in this article. Taking into account the concrete data of research the peculiarities of manifestation of future technology teachers’ self-dependence and experienced emotions in their self-dependent activity are discussed. The researches demonstrate that mare than a half of the students frequently act self-dependently, however self-dependence in the activity of one third of the students is not sufficiently stable. Significant correlation between various forms of self-dependence and self-dependence as an integral characteristic shows that all manifestations identified in the research model may have impact on the encouragement of self-dependence. Most often self-dependence in the students’ activity reveals itself through curiosity, and most seldom it is revealed through creativity. Therefore, seeking to develop self-dependence of technology students it is important to refer to curiosity and organization as well as to pay more attention to the enhancement of initiative and creativity. In the course of a self-dependent activity students frequently experience positive emotions Goy) while negative emotions (sadness) are experienced much more seldom. Students who seldom experience joy in self-dependent activity more seldom act creatively. Therefore, it is very important to enhance positive emotions by looking for new ideas, seeking for new results of activity, acting in unusual situations.